IMPORTANCE AND BENEFITS OF IDIOMS IN LANGUAGE LEARNING - Kokanova Nursuliu Jenisbay qizi; Allanova Munira Mubarak qizi (Scientific Impulse, 2023)
In this article, we describe the importance and stages of idiom analysis for people learning English as a second language, the role of idioms and phraseology in language learning. Today, based on the rapid development of technologies, languages are also developing very quickly, and they have become an integral part of society's life. The fact that many young people can communicate freely in several languages in addition to their mother tongue is their achievement and a solid step for the future.